2009
DOI: 10.1002/path.2520
|View full text |Cite
|
Sign up to set email alerts
|

Current smoking‐specific gene expression signature in normal bronchial epithelium is enhanced in squamous cell lung cancer

Abstract: Cigarette smoking is the main risk factor for the development of squamous cell lung carcinoma (SCC). However, the smoking-related molecular changes in SCC have not been studied. Gene expression studies in both histologically normal bronchial epithelium and SCC epithelial samples identified genes differentially expressed between current and ex-smokers. Subsequently, expression levels of the smoking-related genes in normal bronchial epithelium were compared with those in SCC cells, since we hypothesized that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 45 publications
4
49
1
Order By: Relevance
“…Some of the genes that showed enduring alterations in expression have never been reported to be involved in lung cancer, whereas others are targets of Table 3. Replicated probe sets upregulated by smoking and not returning to never-smoker levels within 10 years of smoking cessation in the discovery set and validated in at least one of the 2 replication sets Most whole-genome gene expression studies that have been done to investigate the impact of tobacco smoking were carried out on airways, (6-14) alveolar macrophages, (15)(16)(17) lung tumors, (7,(18)(19)(20)(21), or peripheral leukocytes (22)(23)(24)(25)(26)(27). The impact of tobacco smoking on gene expression in nontumor lung tissue has been evaluated in only a few studies (18,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the genes that showed enduring alterations in expression have never been reported to be involved in lung cancer, whereas others are targets of Table 3. Replicated probe sets upregulated by smoking and not returning to never-smoker levels within 10 years of smoking cessation in the discovery set and validated in at least one of the 2 replication sets Most whole-genome gene expression studies that have been done to investigate the impact of tobacco smoking were carried out on airways, (6-14) alveolar macrophages, (15)(16)(17) lung tumors, (7,(18)(19)(20)(21), or peripheral leukocytes (22)(23)(24)(25)(26)(27). The impact of tobacco smoking on gene expression in nontumor lung tissue has been evaluated in only a few studies (18,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous transcriptomic studies indicate that a large number of genes are modulated by smoking in airways (6)(7)(8)(9)(10)(11)(12)(13)(14), alveolar macrophages (15)(16)(17), lung tumors (7,(18)(19)(20)(21), and peripheral leukocytes (22)(23)(24)(25)(26)(27). Fewer transcriptomic studies have also examined the effect of the duration of smoking cessation on gene expression profiles (6,8,10,12).…”
Section: Introductionmentioning
confidence: 99%
“…1B, discovery cohorts). For each cohort, we trained classifiers based on various feature selection criteria and classifier models, including previously reported smoking-related gene signatures from both normal and tumor tissues (16,(19)(20)(21)39; Supplementary Fig. S2A and S2B and Supplementary Methods).…”
Section: Supervised Classification Of Smoking Status Based On Gene Exmentioning
confidence: 99%
“…Together, this indicates a significant heterogeneity within smoking-defined subgroups of adenocarcinoma. Numerous studies have reported transcriptional differences between never-smokers and smokers in both normal airway epithelium and adenocarcinoma tumor tissue (16)(17)(18)(19)(20)(21)(22)(23). In addition, gene expression-based molecular subgroups in lung adenocarcinoma, e.g., the bronchioid (24) and terminal respiratory unit (TRU; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Studies dating back to 1977 had already made the link and concluded that "lung cancer and COPD share a common familial pathogenetic component associated with pulmonary dysfunction" [2]. More recent studies have confirmed this pathogenetic overlap with the observation that common bronchial epithelial gene expression signatures exist for (ex)-smoking and squamous cell lung cancer [3]. Emerging evidence suggests that progressive lung scarring in the context of idiopathic pulmonary fibrosis (IPF) similarly represents a risk factor for lung carcinogenesis, although causality remains to be definitively established [4], Given that chronic lung diseases such as COPD and IPF occur more frequently in elderly individuals, and that the hallmarks of ageing are closely linked with the hallmarks of cancer development [5], such an overlap is perhaps not entirely surprising.…”
mentioning
confidence: 65%